Essential Norm of Operators into Weighted-Type Spaces on the Unit Ball - Pablo Galindo; Mikael Lindström; Stevo Stević (Abstract and Applied Analysis)
The essential norm of any operator from a general Banach space of holomorphic functions on the unit ball in ℂn into the little weighted-type space is calculated. Some applications of the formula are given.